NOVEL C-RING CLEAVED TRITERPENOID-DERIVED AROMATIC HYDROCARBONS IN TERTIARY BROWN COALS - de las Heras F.X.; Grimalt J.O.; Albaigés J. (My University, 1991)
Five novel ethylene-linked polymethyl-substituted phenyl/naphthyl or naphthyl/naphthyl hydrocarbons have been identified in aromatic hydrocarbon fractions of immature Tertiary coals using liquid chromatography, gas chromatography (GC), and GC coupled to mass spectrometry. These compounds are produced during coalification through triterpenoid aromatization processes that involve C-ring opening (C8(14) bond cleavage) and preservation or loss of the A-ring. This second type of reaction is illustrated here for the first time. Structures corresponding to various degrees of aromatization have been found, indicating that these hydrocarbons undergo further aromatization after C-ring cleavage. All these compounds are observed to occur only in coals corresponding to diagenetic conditions that have also resulted in the formation of C-ring preserved triterpenoid-derived hydrocarbons containing more than two aromatic rings.